Direct conjugation of antibodies to the ZnS shell of quantum dots for FRET immunoassays with low picomolar detection limits. Issue 100 (30th November 2016) - Bhuckory, S.; Mattera, L.; Wegner, K. D.; Qiu, X.; Wu, Y.-T.; Charbonnière, L. J.; Reiss, P.; Hildebrandt, N.
Abstract : Direct conjugation of IgG, F(ab′)2, and Fab antibodies to the ZnS shells of penicillamine-coated quantum dots for high-sensitivity FRET biosensing. Abstract : Compact and functional nanoparticle-antibody conjugates are of paramount importance for the development of quantum dot (QD)-based immunoassays. Here, we present a simple strategy to directly conjugate IgG, F(ab′)2, and Fab antibodies via their endogenous disulfide groups directly to the inorganic ZnS shell of compact penicillamine-coated QDs. The functionality of the conjugates was demonstrated by terbium (Tb)-to-QD FRET immunoassays against prostate specific antigen in serum samples. Detection limits of 2.5 pM (0.080 ng mL −1 ) were 10 and 25 times lower compared to conjugation via maleimide-terminated ligands and polymer chains, respectively. These more compact, simple, and sensitive QD-antibody conjugates will be highly advantageous for nanocrystal-based biosensing applications.